IKeWYSe – I Know What You See An educational tool for perspective-taking skills - Pio Alfredo Di Tore; Stefano Di Tore; Giuseppina Rita Mangione; Felice Corona; Jordi Conesa Caralt (Je-LKS: Journal of E-Learning and Knowledge Society, 2014)
Research on narrative and interaction with pedagogical studies which refer to disciplines that require strong immersion for the acquisition of knowledge in areas such as museum education lead scholars to question the importance of perspective taking. This work represents the evolution for educational purposes of a narrative video game designed for the measurement of perspective taking skills. Perspective taking skills, or the ability to change point of view, involve the need for a mental rotation, in relation to the environment or to an object in the environment, while maintaining a main perspective environment in question. This is the key feature, for Alain Berthoz, of empathy. Empathy is a dynamic process that requires a doubling, it is to adopt an egocentric point of view, but after an allocentric manipulation, while inhibiting the emotional contagion, which is rather typical of sympathy. Empathy is a process considered to be particularly relevant in the field of education. Historically, the interest of the educational community focused on the empathic abilities of the teacher, primarily due to the influence of the work of Carl Rogers. The main goal of this research is to design an smart environment that allows to intervene in adaptive way on the empathic abilities of the students, working on their perspective taking skills, and to analyze the different building blocks that may be used to create the proposed educational tools. The prototype of the narrative game from which this study started is aimed at assessing the age at which students develop perspective-taking and mental rotation skills. The present study shifts the focus of research from skills measuring to skills training. The specific educational needs have led to a complete re-design of the application and to the introduction of a semantic layer that can adaptively support user whit ad hoc feedback. This paper presents the spatial theory of empathy framework, describes the narrative game prototype, an smart environment aimed at measuring the perspective taking skills, and introduces the design of a specific ontology for the educational version.